2008
DOI: 10.1063/1.2901052
|View full text |Cite
|
Sign up to set email alerts
|

Brownian dynamics simulations of polyelectrolyte adsorption in shear flow: Effects of solvent quality and charge patterning

Abstract: We probe the effects of solvent quality and charge patterning on polyelectrolyte adsorption in shear flow using Brownian dynamics simulations with hydrodynamic interaction (HI). The polyelectrolyte is modeled as a freely jointed bead-rod chain, and electrostatic and non-electrostatic interactions are accounted for by using screened Coulombic and Lennard-Jones potentials, respectively. In the absence of flow, the conformation of a polyelectrolyte molecule adsorbed onto a uniformly charged surface changes from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 72 publications
3
28
0
Order By: Relevance
“…The BD simulation technique has been shown to be very efficient, especially for modeling long biopolymer chains under complex flow conditions [19][20][21][22]. Hydrodynamic interactions (HI) have been confirmed to play an important role in polymer dynamics [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The BD simulation technique has been shown to be very efficient, especially for modeling long biopolymer chains under complex flow conditions [19][20][21][22]. Hydrodynamic interactions (HI) have been confirmed to play an important role in polymer dynamics [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…6, the rescaled velocity V /γz COM , measured along the adsorption transition line, decreases with decreasing interaction range σ W as a result of enhanced surface friction, while the extension in flow direction R S /2N , also measured along the transition line, increases strongly due to internal shear effects in the globule. This means that the inhomogeneous surface enhances unfolding of the FD polymer in shear flow but suppresses adsorption; in other words, the stretching of the chain, which by itself weakens entropic repulsion from the surface and therefore promotes adsorption [34], is overwhelmed by the weakened energetic attraction to the surface since the monomers are constantly pulled away from the surface binding sites [17,14].…”
Section: Fixed Shear Rate Variable Corrugationmentioning
confidence: 99%
“…When considering non-equilibrium effects, e.g. by inclusion of simple shear-flow [12][13][14], it has been shown that hydrodynamic interactions and the presence a e-mail: radtkem@physik.fu-berlin.de of a no-slip boundary is crucial and therefore has to be taken into account [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…(b) E-mail: w.poon@ed.ac.uk be amphoteric, and display a minority of positive charges. At low enough ionicity, the negative polymer segments may adopt loopy configurations to contact the positive surface patches [6], leading to bridging and aggregation. Secondly, polyvalent cations can form salt bridges between negatively charged particles and polymer, once again allowing polymer-induced bridging [7].…”
mentioning
confidence: 99%